The Atypical Guanylate Kinase MoGuk2 Plays Important Roles in Asexual/Sexual Development, Conidial Septation, and Pathogenicity in the Rice Blast Fungus - Cai, Xingjia; Zhang, Xi; Li, Xinrui; Liu, Muxing; Liu, Xinyu; Wang, Xiaoli; Zhang, Haifeng; Zheng, Xiaobo; Zhang, Zhengguang (Frontiers in Microbiology, 2017)
Guanylate kinases (GKs), which convert guanosine monophosphate into guanosine diphosphate (GDP), are important for growth and mannose outer chain elongation of cell wall N-linked glycoproteins in yeast. Here, we identified the ortholog of Saccharomyces cerevisiae GK Guk1, named MoGuk1 and a novel family of fungal GKs MoGuk2 in the rice blast fungus Magnaporthe oryzae. MoGuk1 contains 242 aa with an C-terminal GuKc domain that very similar to yeast Guk1. MoGuk2 contains 810 amino acids with a C-terminal GuKc domain and an additional N-terminal efThoc1 domain. Expression of either MoGuk1 or MoGuk2 in heterozygote yeast guk1 mutant could increase its GDP level. To investigate the biological role of MoGuk1 and MoGuk2 in M. oryzae, the gene replacement vectors were constructed. We obtained the ∆Moguk2 but not ∆Moguk1 mutant by screening over 1000 transformants, indicating MoGuk1 might be essential for M. oryzae. The ∆Moguk2 mutant showed weak reductions in vegetative growth, conidial germination, appressorial formation and appressorial turgor, and showed significant reductions in sporulation and pathogenicity. Moreover, the ∆Moguk2 mutant failed to produce perithecia and was sensitive to neomycin and a mixture of neomycin-tunicamycin. Exogenous GDP and ATP partially rescued the defects in conidial germination, appressorial formation and infectious growth of the mutant. Further analysis revealed that intracellular GDP and GTP level was decreased, and GMP level was increased in the mutant, suggesting that MoGuk2 exhibits enzymatic activity. Structural analysis proved that the efThoc1, GuKc and P-loop domains are essential for the full function of MoGuk2. Taken together, our data suggest that the guanylate kinase MoGuk2 is involved in the de novo GTP biosynthesis pathway and is important for infection-related morphogenesis in the rice blast fungus.